A Qualitative Study on the Role of Big Data Technology in Influencing Capital Structure, Profitability, Dividend Policy, Firm Performance, Firm Value, and Sustainability - Renaldo, Nicholas; Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Andi, Andi; Wahid, Nabila; Cecilia, Cecilia (Luxury: Landscape of Business Administration, 2025)
This study seeks to explore how organizations perceive and utilize Big Data technology in shaping financial and sustainability strategies. This study also develops a new measurement for Big Data Technology variable. This study employs a qualitative research design using a multiple case study approach to gain in-depth insights into how firms adopt and interpret Big Data technology in relation to financial and sustainability outcomes. Data will be transcribed and coded using qualitative analysis software. Big Data Technology have a great effect on Capital Structure, Profitability, Dividend Policy, Firm Performance, Firm Value, and Sustainability. Big Data is not just a technological tool, but a strategic asset that supports integrated decision-making across both financial and non-financial performance areas. Future studies could use quantitative or mixed-method approaches to test hypotheses derived from this qualitative research, such as measuring the impact of Big Data maturity on profitability or ESG scores.